2014
DOI: 10.4315/0362-028x.jfp-13-440
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal Times of Oxytetracycline and Tylosin in Eggs of Laying Hens after Oral Administration

Abstract: Antimicrobials administered to laying hens may be distributed into egg white or yolk, indicating the importance of evaluating withdrawal times (WDTs) of the pharmaceutical formulations. In the present study, oxytetracycline and tylosin's WDTs were estimated. The concentration and depletion of these molecules in eggs were linked to their pharmacokinetic and physicochemical properties. Twenty-seven Leghorn hens were used: 12 treated with oxytetracycline, 12 treated with tylosin, and 3 remained as an untreated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Multiple studies [48][49][50][51][52][53][54][55][56][57][58][59][60] have been performed to evaluate depletion of oxytetracycline residues in the eggs of treated hens. In Canada, oxytetracycline soluble powder is approved for use in the drinking water of laying hens at concentrations ranging from 50 to 112 mg/L (190 to 424 mg/gal) with 60-hour to 5-day egg withdrawal intervals, respectively.…”
Section: Farad Poultry Statisticsmentioning
confidence: 99%
“…Multiple studies [48][49][50][51][52][53][54][55][56][57][58][59][60] have been performed to evaluate depletion of oxytetracycline residues in the eggs of treated hens. In Canada, oxytetracycline soluble powder is approved for use in the drinking water of laying hens at concentrations ranging from 50 to 112 mg/L (190 to 424 mg/gal) with 60-hour to 5-day egg withdrawal intervals, respectively.…”
Section: Farad Poultry Statisticsmentioning
confidence: 99%
“…Munoz et al. () evaluated the depletion of oxytetracycline and tylosin in egg white and yolk. They found that the drugs were present in greater amounts in the egg yolk than in the white and also remained for longer in the yolk.…”
Section: Resultsmentioning
confidence: 99%
“…The primary reason for the differences in the conclusions of the studies mentioned above is probably the fact that they investigated different drugs and were performed under different experimental conditions. In addition, multifactorial causes including the oral bioavailability of the investigated drug and its physiochemical properties (molecular weight and solubility), the physiology of the chicken specimens as well as differences in the egg formation properties, organ perfusion characteristics, and tissue composition could also be likely reasons (Alaboudi, Basha, & Musallam, ; Bilandzic et al., ; Donoghue & Myers, ; Kan, ; Munoz et al., ). Roudaut and Moretain () stated that the differences in the sensitivities of the analytical methods used to detect drugs in egg matrices could also be a reason for the differences observed in their deposition patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tylosin is widely used as antimicrobial agent in China and administered through pareteral or oral route. The Pharmacokinetics study of tylosin has been described in a variety of animals including hens [ 14 ], broiler chickens [ 15 ], goats [ 16 ], cows [ 17 ] and dog [ 18 ]. However, there are limited data available on the Pharmacokinetics/pharmacodynamics model of tylosin in pigs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%